Learning from deaths in the NHS: a new but necessary challenge. Issue 5 (25th September 2018) - Bourke, Trisha; Vale, Justin
Abstract : Since 2016 NHS organisations have been expected to review all deaths and assess avoidability. This is a significant task and presents many challenges. However, as Justin Vale discusses in this article it is a vital part of the learning process.